A mortal case of coronavirus disease in a pregnant diabetic woman. Clinical case - K. Uzel; I. V. Lakhno (Publishing House TRILIST, 2020)
Pregnant women are very susceptible to coronavirus infection. Gestational diabetes mellitus is severe comorbidity and a serious risk factor for lethal outcomes. We report a mortal case of coronavirus disease (COVID-19) associated with bilateral pneumonia and systemic inflammatory response syndrome in a pregnant woman with gestational diabetes mellitus. Patient was admitted to the hospital at 31 weeks of gestation with COVID-19 bilateral pneumonia. Anti-inflammatory, antiviral, antibacterial and immunomodulatory treatment was started. She received per os favipiravir 200 mg, azithromycin 500 mg, enfluvir 75 mg, plaquenil 200 mg, and ceftriaxone 1 g intravenously, piperacillin 4.5 g intravenously, methylprednisolone 40 mg intramuscular, enoxaparin 0.6 subcutaneously. The doses of insulin were changed. But maternal status became worse in several hours. Oxygen saturation dropped to 80%. Patient was intubated and connected to the artificial lung ventilator. The cesarean was performed. The preterm born baby with early neonatal sepsis diseased the next day. The treatment could not counteract an inflammatory storm. Despite intensive resuscitation, the woman diseased. The fatal case of COVID-19 was associated with coexisted gestational diabetes mellitus and late admission to the hospital. The COVID-19 patients with gestational diabetes mellitus are at higher risk of severe pneumonia, systemic inflammatory response and carbohydrate metabolism decompensation. Oxidative stress caused by bilateral pneumonia initiated the chain of tissue injury-related reactions. The fat tissue is an additional source of free radicals and proinflammatory cytokines. Progression of the proinflammatory scenario enhanced multiple organ failure. We have found signs of acute pulmonary, hepatic, and renal insufficiency. The unresponsiveness to treatment contributed to systemic inflammatory response and maternal deterioration. Further investigations are necessary to improve outcomes in COVID-19 during pregnancy.